Analysis of Intra- Cultivar Heterogeneity in Dashehari Mango (Mangifera Indica L.) by Using Scanning Electron Microscopy - Kishor, S; Dwivedi, Deepa H; Maji, S; Ahirwar, CS (Bangladesh Journal of Botany, 2024)
The present study aimed at estimating intra-cultivar heterogeneity in Dashehari cultivar of mango (Mangifera indica L.) by using Scanning Electron Microscopy (SEM). Forty-five trees of 25-30 years old, from 15 orchards in Malihabad and Mall blocks of district Lucknow, Uttar Pradesh were selected for study which revealed a significant variation in all stomatal characteristics. Phenotypic and Genotypic coefficient of variation (PCV and GCV, respectively) values for these parameters were very close, indicating that they were controlled at genetic level and were independent of environmental effect. Highest phenotypic (41.59) and genotypic (38.27) coefficient of variation, and Genetic advance as percent of mean (GAM) (149.41 %) were recorded for stomatal pore size (width) while highest (97.50) heritability (h2) and genetic advance (20.86) were observed for stomatal density. Dendrogram clusters of the Dashehari population under study, prepared based on stomatal observations, divided into two main clusters which further divided into sub-clusters. The study on stomatal characters is fully facilitated by SEM and hence, it is suggested that SEM may be a useful tool for identification of intra-varietal variability of Dashehari mango for further crop improvement programme. Bangladesh J. Bot. 53(2): 391-399, 2024 (June)